INSTITUT AGAMA ISLAM NEGERI (IAIN) DAN PEMBANGUNAN ETOS KERJA KEILMUAN - Safira, Juwaini (UIN Ar-Raniry, 2014)
The development of information and communication technology has brought a change in materialism and pragmatismtrend. Material satisfaction is increasingly becoming an obsession even at the sacrifice of his moral life. This phenomenon occurs not only in politics or government bureaucracy, but also a lot of education and college academic community. In this regard the efforts of revitalization work ofÃ‚Â ethic paradigm based on religious morality becomes important to beÃ‚Â strengthened. The Expectation from this community effort that the academic community based on intellectual integrity and academic honesty. This work ethic can be developed through moral and religious consciousness that work only to get Allah's approval.